The Virtual Initial Reading Teaching and Learning Process during the COVID-19 Pandemic - Widiastika, Wasi; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
One aspect that is seriously affected by the COVID-19 pandemic is the continuity of education's teaching and learning process, especially in the initial reading. This study explores initial reading teaching activities, which are currently mainly carried out virtually in terms of virtual platforms used, methods, learning resources, the conveniences, and obstacles faced by the teachers in several schools. The research method used was a Survey with a cross-sectional survey design. Research data was obtained online by using google form media. The respondents involved in this study were 18 elementary school teachers who taught in the lower grades and came from 18 different elementary schools. The results showed that in teaching and learning initial reading virtually, the platform used was WhatsApp video call, the most widespread method used was the syllable method, and the most widely used learning resource was textbooks provided by the school. The convenience faced by teachers when carrying out virtual reading lessons is the availability of flexible time in teaching activities. In contrast, the limited teaching time, the unstable internet connections, and the limitations of the facilities also infrastructure owned by parents become the obstacles to the virtual initial reading learning process.